Spin‐ and Voltage‐Dependent Emission from Intra‐ and Intermolecular TADF OLEDs. (18th January 2021) - Bunzmann, Nikolai; Krugmann, Benjamin; Weissenseel, Sebastian; Kudriashova, Liudmila; Ivaniuk, Khrystyna; Stakhira, Pavlo; Cherpak, Vladyslav; Chapran, Marian; Grybauskaite‐Kaminskiene, Gintare; Grazulevicius, Juozas Vidas; Dyakonov, Vladimir; Sperlich, Andreas
Abstract: Organic light emitting diodes (OLEDs) based on thermally activated delayed fluorescence (TADF) utilize molecular systems with a small energy splitting between singlet and triplet states. This can either be realized in intramolecular charge transfer states of molecules with near‐orthogonal donor and acceptor moieties or in intermolecular exciplex states formed between a suitable combination of individual donor and acceptor materials. Here, 4, 4′‐(9H, 9′H‐[3, 3′‐bicarbazole]‐9, 9′‐diyl)bis(3‐(trifluoromethyl) benzonitrile) (pCNBCzoCF3 ) is investigated, which shows intramolecular TADF but can also form exciplex states in combination with 4, 4′, 4′′‐tris[phenyl(m‐tolyl)amino]triphenylamine (m‐MTDATA). Orange emitting exciplex‐based OLEDs additionally generate a sky‐blue emission from the intramolecular emitter with an intensity that can be voltage‐controlled. Electroluminescence detected magnetic resonance (ELDMR) is applied to study the thermally activated spin‐dependent triplet to singlet up‐conversion in operating devices. Thereby, intermediate excited states involved in OLED operation can be investigated and the corresponding activation energy for both, intra‐ and intermolecular based TADF can be derived. Furthermore, a lower estimate is given for the extent of the triplet wavefunction to be ≥ 1.2 nm. Photoluminescence detected magnetic resonance (PLDMR) reveals the population of molecular triplets in optically excited thin films. Overall, the findings allow to draw a comprehensive picture of the spin‐dependent emission from intra‐ and intermolecular TADF OLEDs. Abstract : A molecular thermally activated delayed fluorescence emitter for sky blue organic light emitting diodes (OLEDs) is studied. When combined with m‐MTDATA, additional orange emission from interfacial exciplex states is observed which enables warm‐ to cold‐white OLEDs with voltage‐dependent color tuning. Excitation pathways for electrical generation and optical excitation are resolved using spin‐sensitive magnetic resonance techniques.